IMPACT OF CLIMATE CHANGE ON WATER SECURITY IN KRISHNA RIVER BASIN, INDIA - Uniadi Mangidi (STABILITA || Jurnal Ilmiah Teknik Sipil, 2013)
AbstractClimate change have been an  increasing concern worldwide and affects to almost all areas of life. One of the most vulnerable sectors from climate change is water resources both availability and demand. This is due to climate change generate extreme events (intensity and magnitude) and leading to flooding and drought. While most tropical regions experience flooding, semi arid ones, such as India, are hit by extreme drought and so influence their water balance.  In supply side, it will increse the proportion of evapotranspiration then reducing streamflow. By the fact that streamflow is the primary source to meet water demands, under such condition will enhance the unmet demand due to limited supply and as are result,it increases the competition among water stakeholders leading to conflict of intertest. Krishna river basin in India,  is one of catchment area that clearly show such conflict and it seems that it will exist in the future with larger impact, particularly if the improved  prediction of climate change in water sector does not developed. This research aims to predict the impact of climate change on water sector and predict the water balance until 2030. To get the expected result, it is applied a tool (WEAP Model). The result show that the security of inflows into the reservoirs is not guaranteed in the future, due to the trends in change in climate and its impact on runoff. Therefore a hypothetical scenario was implemented in the model with a 10 % reduction in stream flow and 1 degree rise in temperature. One degree rise in temperature is equivalent to the 8 % increase in evaporation and evapotranspiration.  Total unmet demand rise noticeably to more than double at 58 %, from 120.51 BCM (baseline) to 190.80 BCM during the period from 2002 to 2030. The average annual unmet demand also increased by 62 %. The results indicate that shortfall occurs every year in the irrigation sector. The return period of demand deficit of more than 1000 Mm3 occur in Almatti and Tunga Bhadra once in 10 years (90% assurance). The Upper Krishna power generation is severely affected where the shortfall of more than 1000 and 550 MCM occurs once in 10 and 3 years respectively AbstrakPerubahan iklim telah menjadi isu yang sangat penting dan mempengaruhi dihampir semua sektor kehidupan. Salah satu  sektor yang paling rentan terhadap perubahan iklim adalah sektor sumber daya air . hal ini karena fenomena perubahan iklim itu memicu cuaca ekstrim (intensitas dan besarannya) diberbagai belahan dunia yang mengakibatkan banjir dan kekeringan. Jika di daerah tropis sering terjadi banjir, maka sebaliknya daerah sub tropis seperti India, fenomena kekeringan merupakan dampak yang terlihat dan memperngaruhi keseimbangabn air (pasokan dan kebutuhan). Disisi pasokan, perubahan iklim mengakibatkan meningkastnya proporsi evapotranpirasi, selanjutnya menurunkan jumlah kpasokan air disungai.  Daerah aliran sungai Krishna di India merupakan DAS yang sangat penting sekaligus sangat rentan terhadap ancaman kekeringan. Hal ini diakibatkan oleh meningkatnya kebutuhan disatu sisi dan berkurangnya ketersediasan disisi yang lain. Oleh karena itu, upaya-upaya mitigasi dan adaptasi harus dilakukan guna mengurangi damapak yang lebih besar dimasa datang. Agar upaya tersebut tepat sasaran maka diperlukan evsluasi terhadap ketersedian tentang ketersediaan saat ini dan selanjutnya prediksi keseimbangan air dimasa datang. Dengan menggunakan bantuan perangkat lunak WEAP, diperoleh hasil bahwa ketersediaan inflow yang masuk ke waduk tidak terjamin diakibatkan oleh perubahan iklim dan pengaruhnya terhadap run off. Peningkatan satu derajat suhu dibumi ekivalen dengan penurunan 8 % evaporasi dan evapotranspirasi, sehingga mengakibatkan penurunan 10 % aliran di sungai. Akibat dari penurunan tersebut, maka jumlah kebutuhan yang tidak terpenuhi meningkat lebih dari dua kali lipat atau 58 %, dari 120.51 miliar kubik ke 190.80 miliar kubik selama periode 2002 ke 2030. Sedangkan jumlah rerata kebutuhan yang tidak terpenuhi juga meningkat sebesar 62 %. Hasil ini menindikasikan bahwa akan terjadi kekurangan opasokan air setiap ntahun  pada sektor irigassi. Periode ulang dari kekurangan air  lebih dari 1000 m3 akan terjadi di Almatti dan Tunga Bhadra sekali dalam 10 tahun (90 %). PLTA di hulu DAS Krishna akan sangat terpengaruh dimana kekurangan yang lebih dari 1000 dan 550 miliar kubik terjadi sekali dalam 10 dan 3 tahun berturut-turut. Kata Kunci: Climate changes, Water security, WEAP